MENINGKATKAN MOTIVASI BELAJAR BAHASA INGGRIS MELALUI PERMAINAN â€œCHARADESâ€ PADA SISWA KELAS 5 SDN 3 TEMBUKU, BANGLI DI ERA NORMAL BARU - Ni Putu Yeni Yuliantari; Putu Cita Ayu; Putu Nuniek Hutnaleontina; Ni Made Wisni Arie Pramuki; Ni Putu Ayu Kusumawati (JURNAL SEWAKA BHAKTI, 2021)
The lack of facilities (such as smartphone or internet signal) and parental assistance during the learning process from home made it difficult for subject materials to be conveyed properly, especially in English lessons. This can be decreased the students' interest and ability in that lesson and continued to face-to-face (offline) meetings. If this happens in the beginning stage, then the students will have difficulty in following the next stages. In order to increase the studentsâ€™ interest and motivation in learning English, this community service is held. Through the games "Charades", students can learn English using their physical language and verbal language. Students can also move actively so that their friends are able to guess the hidden words. The results of this community service activity is it can increase the interest and motivations of 5th grader at SDN 3 Tembuku, Bangli in learning English and they also understand the materials given.